Islam dan Moderasi Beragama: Analisis Tafsir Maudhu’i - Fitria Fitria; Khoirunnisa Khoirunnisa; Luthfi Miftahul Anwar; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
This research is aimed at explaining issues related to religious moderation in the views and interpretations of the Qur'an. Using a library approach method by applying the descriptive-analytical method. The Qur'an and its interpretations are the formal object of this study, while the material object is the verses of the Qur'an using the maudhu'i interpretation method. The results and research show that there are several verses that are relevant to the issue of religious moderation, such as: (Q.S al-Baqoroh: 143, Q.S an-Nisa: 58). This study concludes that these verses are very relevant to existing problems, especially on the issue of religious moderation, and it is hoped that these verses can add insight, views, and information for us to solve problems regarding religious moderation.